Intrinsic Motivation for Chinese Fansub Groups and Copyright Issues in the Digital Age - Liu, Qinqin (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Andalas, 2024)
Fansubs are very popular these days in China because of the general public's expanding cultural need. However, the behavior of producing fansubs constitutes a violation of copyright law in essence both in China and in the world since all the audiovisual materials translated and distributed in China have not obtained authorization from copyright owners of foreign movies and television shows. The aim of this study is to explore the reasons why fansub groups in China would keep distributing foreign films and TV shows online with subtitles translated by them despite concern over piracy and copyright. This paper would adopt a method of qualitative research with a focus on content-analysis by observing and analyzing highly relevant discussions on Zhihu, Weibo and Douban, which are Chinese online platforms where users can engage in discussions on various topics. Based on observation and analysis, the paper would discuss the phenomenon of fansubbing in terms of three aspects: awareness of copyright infringement, intrinsic motivation for participation and material considerations. By examining the reasons for fansubber participation and the operation mechanism for this practice situated in a copyright environment, the paper hopes to come up with possible suggestions for protecting the intrinsic motivation for fansubbers while enhancing legal justice, order of the market and creativity of the society.